The Effect of GSR Biofeedback Relaxation on Anxiety and Stress in Patients with Type II Diabetes Mellitus: A Randomized Controlled Trial - Mahendra Kumar; Priyamvada Shrivastava (Shiraz University of Medical Sciences, 2022)
Background: Anxiety disorders have high prevalence in diabetes patients and low-middle income countries like India. Research has provided evidence about biofeedback effectiveness on stress-related psychophysiological parameters. This study aimed to verify the impact of GSR biofeedback relaxation on stress-related psychophysiological parameters (galvanic skin resistance, stress, and anxiety) among type II diabetes patients with high levels of anxiety. Methods:  The present study was a single-blinded randomized controlled trial. Initially, 228 type II diabetes patients were assessed with the state trait anxiety inventory (STAI). Seventy participants identified as having high anxiety with STAI scores above the 75th percentile were invited to participate. Patients were randomly divided into a biofeedback relaxation and a sham-control group. Participants of the biofeedback group received training on how to use the GSR biofeedback device for management of stress parameters for twenty 30-minute sessions. The sham-control group received no intervention. Both groups were assessed before and after the biofeedback relaxation training program. The results of the STAI, GSR, and the inventory of stress for type II diabetes patients were compared. SPSS 16 version was used for analysis. Results: The biofeedback group reported a significant change in the state of anxiety (t=5.089; p <0.001), GSR (t=-2.199; p <0.035), and stress (F=46.850; p <0.001) post-test. The control group reported a moderate increase in stress and trait anxiety at the same time. These results are consistent with previous studies. Conclusion: Biofeedback relaxation is a useful technique for managing stress and anxiety in diabetes type II patients. During an emotional disturbance, it may also be helpful in promoting overall psychological health. Further research is necessary to determine the long-term effects of GSR biofeedback relaxation and the effects of cortisol on mood among diabetes patients.